2009
DOI: 10.1186/1472-6963-9-151
|View full text |Cite
|
Sign up to set email alerts
|

Direct costs associated with the appropriateness of hospital stay in elderly population

Abstract: Background: Ageing of Mexican population implies greater demand of hospital services. Nevertheless, the available resources are used inadequately. In this study, the direct medical costs associated with the appropriateness of elderly populations hospital stay are estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…At least 4 studies referred to the cost of inappropriate admissions for specific health conditions of surgical procedures …”
Section: Resultsmentioning
confidence: 99%
“…At least 4 studies referred to the cost of inappropriate admissions for specific health conditions of surgical procedures …”
Section: Resultsmentioning
confidence: 99%
“…In our study, the median length of hospital stay in the total cohort was 9.0 (4.0;16.0) days which is comparable to other older patient cohorts. The median stay in hospital was between 5 and 14 days in older patients admitted to geriatric and internal medicine wards [8,17,22,43,44]. In a previous study analyzing 419 patients aged ≥70 years from geriatric wards [28], higher age, number of admission diagnoses, incontinence, and ADL impairment predicted a longer hospital stay.…”
Section: Comparison With Literature Length Of Hospital Staymentioning
confidence: 94%
“…The need of intensified medical care in older patients as reflected by prolonged length of hospital stay, more nursing hours and patients receiving physiotherapy challenges personnel and financial resources [8,17,18]. Previous studies have shown that prolonged length of hospital stay is predicted by factors including female sex and polypharmacy in patients aged ≥65 years admitted to acute internal and geriatric wards [8] and by age ≥ 60 and higher number of comorbidities in colon cancer patients aged < 60 to > 80 years [19].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the median length of hospital stay in the total cohort was 9.0 (4.0;16.0) days which is comparable to other older patient cohorts. The median stay in hospital was between 5-14 days in older patients admitted to geriatric and internal medicine wards [8,17,22,43,44]. In a previous study analyzing 419 patients aged ≥70 years from geriatric wards [28], higher age, number of admission diagnoses, incontinence, and ADL impairment predicted a longer hospital stay.…”
Section: Length Of Hospital Staymentioning
confidence: 99%